Determinants of Deposit Potential as Inverse Liquidity Indicator of Commercial Banks in Serbia - Milošević Avdalović, Snežana; Kalaš, Branimir (Industrija, 2016)
The aim of this paper is to identify determinants of liquidity of commercial banks in the Republic of Serbia, observing the macroeconomic and banking-specific indicators, or micro-economic indicators which were analyzed by descriptive statistics, correlation and regression analysis from 2008 to 2014. The correlation for the observed variables is calculated from 140 samples for internal and external independent variables of impact to the dependent variable – liquidity measured by indicator of deposits. The subject of research is the process of optimization model reducing the factors of liquidity to variables that have the most significant impact on liquidity indicator measured by deposit potential. Results of the model show that liquidity of banks is dominantly determined by the size of banks assets. With growth of the assets, banks are exposed to a greater risk of liquidity. The increase in capital adequacy ratio has a positive effect on the liquidity of banks. Net interest margin is positively correlated with the indicator of deposit potential which indicates a negative impact on the liquidity of banks as well as the ratio of operating expenses to operating income.
Keywords: Descriptive statistics; Correlation; Multiple regression; Saving deposit; Bank liquidity